DAMPAK AKIBAT AKTIFITAS PENAMBANGAN PASIR DI KOTA SORONG - Asriadi Asriadi; Irwan Ridwan Rahim; Abdul Rahman Djamaluddin (Jurnal Inovasi Pendidikan dan Sains, 2023)
Sand is one of main material for construction. The need of sand is very high for construction development in Sorong for structure or infrastructure work. The research aimed (1) to analyze how wide is the economic impact of the on the community as the result the activties of the sand mines; and (2) to suggest processing management in order to overcome the flood impact on the sand mining activities in sorong city, particularly in kilometer 10 area of Kampung Bugis. the research design was in the formof work program which was arranged so that research could be carried effectively and efficiently. in the stage, the aerialgraphy and overlay of the map of the mine region so that the extent of the mine from year to year could be identified. the research stages were group into the library studym data collection, survey and field observation. and the tecnique of data analysis used the method of eclac and ahp. the research result indicated tha extent of the mining had reached 60%, and consequently the area of flood puddle had increase to80%. the cost had also increased every year, and highest increase occured in 2016, when the cost of the damage and loss wass Rp 12.6 billion, and the cumulative cost had reached Rp 77.14 billion. the management effort to overcome the flood could be divided into 5 criteria of the management efforts, namely costs, availability, realization, time and friendly enviroment, with 3 alternatives, legal reinforcement, construction of structures and social engineering. thus, itt can be include tha the occurance of the flood was influenced by the extent of the sand mining, sothat the sediment scraping reduced the capacity of the river retain water.